2021
DOI: 10.3390/biom11010066
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Conservative Cysteine of Oncomodulin as a Feasible Redox Sensor

Abstract: Oncomodulin (Ocm), or parvalbumin β, is an 11–12 kDa Ca2+-binding protein found inside and outside of vertebrate cells, which regulates numerous processes via poorly understood mechanisms. Ocm consists of two active Ca2+-specific domains of the EF-hand type (“helix-loop-helix” motif), covered by an EF-hand domain with inactive EF-hand loop, which contains a highly conservative cysteine with unknown function. In this study, we have explored peculiarities of the microenvironment of the conservative Cys18 of reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Disulfide bonds in these proteins are commonly formed by conserved cysteine residues localized in their non-functional EF-hands. Consistently, it has been suggested that in the course of evolution, they sacrificed the ability to bind calcium to acquire redox sensitivity [60]. However, such a tendency is not always observed, even within the NCS family: NCS-1 and recoverin form disulfide dimers via their single conservative cysteine in EF1, whereas VILIP-1 uses its unique C-terminal cysteine [28,30,31].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Disulfide bonds in these proteins are commonly formed by conserved cysteine residues localized in their non-functional EF-hands. Consistently, it has been suggested that in the course of evolution, they sacrificed the ability to bind calcium to acquire redox sensitivity [60]. However, such a tendency is not always observed, even within the NCS family: NCS-1 and recoverin form disulfide dimers via their single conservative cysteine in EF1, whereas VILIP-1 uses its unique C-terminal cysteine [28,30,31].…”
Section: Discussionmentioning
confidence: 88%
“…This study is the first to discover that ubiquitous neuronal Ca 2+ -sensor protein NCS-1 possesses redox sensitivity in response to oxidizing conditions by the formation of disulfide dimers with altered structural properties and functional activity. In this respect, NCS-1 resembles some members of the NCS family (recoverin and VILIP-1) and several other EF-hand proteins, such as S100 proteins, oncomodulin, secretagogin, and others [27,28,[30][31][32][33][59][60][61]. Disulfide bonds in these proteins are commonly formed by conserved cysteine residues localized in their non-functional EF-hands.…”
Section: Discussionmentioning
confidence: 99%
“…Another pronounced difference from other parvalbumins is the possession of F18 instead of C18, although a very few α-parvalbumins do have C18 and a very few non-α parvalbumins lost C18 ( Supplementary File S3 ). The C18 residue can be used for cysteine-bridged homodimer formation [ 99 , 100 ], but that does not seem to be the natural situation [ 10 , 95 , 101 ], and, instead, C18 may have a redox sensory function [ 102 ]. Figure 9 D shows that both C18 and F18 insert into the space between the α-helices A and B, and especially F18 may stabilize the contact between these helices.…”
Section: Resultsmentioning
confidence: 99%
“…The α-parvalbumin isoform is found in skeletal muscles, GABAergic neurons, and the outer and inner hair cells of the cochlea. Although β-parvalbumin is restricted to the outer hair cells of the cochlea, it is expressed and secreted by macrophages and neutrophils, serving as a neuronal growth factor (Vologzhannikova et al, 2021). Most of the GABAergic synaptic inhibition throughout the neocortex and hippocampal formation is thought to originate from a heterogeneous population of locally projecting interneurons (Ben-Ari et al, 2021), including parvalbuminexpressing cells (Tremblay et al, 2016).…”
Section: Parvalbumin: Structure and Functionmentioning
confidence: 99%
“…The α-parvalbumin isoform is found in skeletal muscles, GABAergic neurons, and the outer and inner hair cells of the cochlea. Although β-parvalbumin is restricted to the outer hair cells of the cochlea, it is expressed and secreted by macrophages and neutrophils, serving as a neuronal growth factor ( Vologzhannikova et al, 2021 ).…”
Section: Parvalbumin: Structure and Functionmentioning
confidence: 99%